Fuzzy Logic Analysis for Key Factors for Customer Loyalty in E-Shopping Environment - Guo, Li-Xin; Lin, Chih-Chen; Huang, Po-Fang; Jhou, Shou-Yueh; Chen, Shih-Chih; Tsai, Fu-Sheng (Frontiers in Psychology, 2021)
Abstract— Due to subjective evaluation and qualitative characteristics, the assessment processes of loyalty often cannot use the crisp value to express the final value. That makes the evaluation of online store performance usually filled with uncertainty and ambiguity. The loyalty assessment of electronic shopping is complex, and online stores’ strategy and production control problems are frequently accompanied by uncertain conditions. This study constructs a conceptual model to leverage the fuzzy logic approach for understanding the consumers’ decision-making in the e-service context of shopping. This study also exposes the relationships between system quality, information quality, and service quality to understand their impacts on customer loyalty. Implications and future research directions for service providers and researchers are discussed.